C:N:P stoichiometry in China's forests: From organs to ecosystems. (25th September 2017) - Zhang, Jiahui; Zhao, Ning; Liu, Congcong; Yang, Hao; Li, Meiling; Yu, Guirui; Wilcox, Kevin; Yu, Qiang; He, Nianpeng
Abstract: Ecological stoichiometry connects different levels of biology, from the gene to the globe, by scaling up elemental ratios (e.g. carbon [C], nitrogen [N] and phosphorus [P]). Thus, ecological stoichiometry could be a powerful tool for revealing certain physiological processes of plants. However, C:N:P stoichiometry remains unclear at the community and ecosystem levels, despite it being potentially important for primary productivity. In this study, we measured the C, N and P contents of different plant organs, litter and soil in nine natural forest ecosystems (from cold‐temperate to tropical forests along a 3, 700‐km transect in China) to explore C:N:P stoichiometry and the main influencing factors. C:N:P stoichiometry was evaluated for different components in the forest ecosystems (plant community, soil, litter and ecosystem) and, at the community level, for different organs (leaves, branches, trunks and roots) from 803 plant species. The ratios of C:P and N:P decreased with increasing latitude, with spatial patterns being primarily regulated by climate. Interestingly, the homeostasis of N, P and N:P was highest in leaves, followed by branches, roots and trunks, supporting the hypothesis that more active organs have a higher capacity to maintain relatively stable element content and ratios. At the community level, the leaf N:P ratio indicated increasing P limitation in forests of lower latitude (i.e. more southerly) in China's forests. Our findings demonstrate the spatial patterns of C:N:P stoichiometry and the strategies of element distribution among different organs in a plant community, providing important data on C:N:P to improve the parameterization of future ecological models. A plain language summary is available for this article. Abstract : Plain Language Summary